2021
DOI: 10.3390/ijerph18010331
|View full text |Cite
|
Sign up to set email alerts
|

Inculcation of Green Behavior in Employees: A Multilevel Moderated Mediation Approach

Abstract: In this era of globalization, preventing organizations from undermining and degrading the environment has become a great challenge, especially when considering that organizations are among the major contributors to environmental deterioration. As a result, scholars have recently begun to focus on understanding the key determinants of employee green behavior (EGB), a nascent field within the area of sustainable development and organizational behavior. This study extends the emerging discussion over EGB by inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 89 publications
3
33
0
2
Order By: Relevance
“…The results revealed that ETFL has a significant impact on EP, which is in line with the previous research conducted by Robertson and Barling (2013) on the under-grad students in Canada. Also, Saleem et al (2021) reported a positive effect of leadership on employees' environmental behavior. These findings are also consistent with the TL theory, whereby through idealized influence, inspirational motivation, intellectual stimulation and individualized consideration, the organizational leaders inspire the employees to go beyond their personal needs and in process, demonstrate EP to cater to environmental needs (Changar and Atan, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The results revealed that ETFL has a significant impact on EP, which is in line with the previous research conducted by Robertson and Barling (2013) on the under-grad students in Canada. Also, Saleem et al (2021) reported a positive effect of leadership on employees' environmental behavior. These findings are also consistent with the TL theory, whereby through idealized influence, inspirational motivation, intellectual stimulation and individualized consideration, the organizational leaders inspire the employees to go beyond their personal needs and in process, demonstrate EP to cater to environmental needs (Changar and Atan, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…PGC improves environmental motivation and also satisfies employees to work pleasurably toward environmental goals (Amrutha and Geetha, 2021; Norton et al , 2017). The PEB literature also suggests that an organization's environmental policies have a positive effect on employee's green behaviors (Islam et al , 2018; Kong et al , 2021; Saleem et al , 2021). However, since the role of psychological factors is potentially important in understanding PEBs (Li et al , 2019) we, therefore, tested the impact of employee perceptions of an organization's environmental policies as a more proximal micro-level predictor of employee attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the inclusion of ethical leadership as a mediator in the proposed relationship from the perspective of the banking sector also provides a unique insight into the existing literature on CSR and organizational management. There have been different studies highlighting the importance of ethical leadership to promote the pro-environmental behavior of employees in the era of industry 4.0 [142][143][144][145]. However, the banking sector has remained deprived and has not receive due attention in this regard.…”
Section: Discussionmentioning
confidence: 99%